Access to Preventive Health Services of People with Intellectual Disability in Italy - Rosano, Aldo; Battisti, Alessandra (Journal of Intellectual Disability - Diagnosis and Treatment, 2017)
People with intellectual disabilities today have an high life expectancy, routine screening and preventive services are essential to their overall quality of care. We used the 2012-2013 Italian National Health Interview Survey (NHIS) to examine screening and preventive service use for persons with intellectual disability. We estimated about 953 thousand people with intellectual disability, 58% of which are female and the 59% are over 65 years. Their quality of life, in terms of physical and mental status, was significant lower than general population. Intellectually disabled women generally reported screening and preventive services at lower as compared to women without intellectual disability: the risk of not attending a Pap smear test in a due time, in terms of odds ratio, was 4.5 (95% confidence interval, 3.6-5.7), as for mammography was 2.4 (95% confidence interval, 1.8-3.2). The risk of not attending colorectal screening was also significant, even if lower than female screening, (OR: 1.5; 95% confidence interval, 1.2-2.0). Various approaches can be adopted to improve access for intellectually disabled persons to preventive health care services.